2020
DOI: 10.18502/ijps.v15i3.3820
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Obsessive Compulsive Disorder (OCD)

Abstract: Objective: Handwashing is now considered as one of the best safety measures to prevent COVID-19 infection. The effect of excessive handwashing for health on OCD patients who are already having washing compulsion is not known. Furthermore, the fear of contamination of COVID-19 in patients who already have obsession of contamination is not known. This study aims to evaluate the effect of COVID-19 on OCD patients. Method: Phone interviews were done with 84 patients previously diagnosed with obsession of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
90
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(103 citation statements)
references
References 20 publications
6
90
2
5
Order By: Relevance
“…Obsessive‐compulsive disorder (OCD) was diagnosed for a few percent of subjects and it was mainly reported by female subjects. Effect of COVID‐19 on symptoms exacerbations for subjects suffering from OCD was evaluated by Chakraborty et al and findings of the study indicated that a few percent (6%) of COVID‐19 subjects had a worsened symptoms 19 …”
Section: Discussionmentioning
confidence: 99%
“…Obsessive‐compulsive disorder (OCD) was diagnosed for a few percent of subjects and it was mainly reported by female subjects. Effect of COVID‐19 on symptoms exacerbations for subjects suffering from OCD was evaluated by Chakraborty et al and findings of the study indicated that a few percent (6%) of COVID‐19 subjects had a worsened symptoms 19 …”
Section: Discussionmentioning
confidence: 99%
“…Corona COVID-19 pandemic is expected to have a negative effect on OCD patients and medical students firstly as a general stressor on health and communities, secondly by the closure of medical schools and the shifting toward online learning, and lastly by the increasing efforts of handwashing and general hygiene as an essential step in COVID-19 prevention which might trigger the obsession with contamination and compulsive washing of hands. Which are reported as the most common symptoms of OCD [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, previous similar studies were conducted in Israel [ 4 ], Italy [ 5 ], India [ 6 ], and Japan [ 7 ], whereas most participants in our survey were from the United States. The mental health toll of COVID-19 is inextricable from location-specific factors; these include government decisions about the pandemic, media reports that might influence beliefs and reduce or increase psychological distress [ 12 ], and co-occurring collective challenges such as political unrest [ 13 ].…”
Section: Discussionmentioning
confidence: 94%
“…Several surveys among people with OCD were conducted between April and May 2020 in Israel [ 4 ], Italy [ 5 ], India [ 6 ], and Japan [ 7 ] to explore how OCD symptoms had changed since the onset of the pandemic. About 7%-37% of the participants in these surveys experienced worsening OCD symptoms since the COVID-19 pandemic began.…”
Section: Introductionmentioning
confidence: 99%